2000
DOI: 10.1007/s004280000234
|View full text |Cite
|
Sign up to set email alerts
|

Association of human papillomavirus infection with carcinoma of the cervix uteri and its precursor lesions: theoretical and practical implications

Abstract: Human papillomaviruses (HPVs) are the major aetiological agents of cervical carcinoma. In this review, epidemiological and molecular data are combined to present a model for HPV-induced cervical carcinogenesis. The impact of current knowledge regarding diagnostic and therapeutic approaches is shown, i.e. the use of HPV tests in cervical cancer screening, in the management of atypical smears of uncertain diagnosis and in smears indicative of mild dysplasias, as well as in follow-up examinations during and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
11

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 68 publications
2
32
0
11
Order By: Relevance
“…Previous studies indicated that 50% of the HPV transient infections disappear within a few months in most cases, despite the presence of oncogenic virus, probably as a result of a competent host immune response [25,26].…”
Section: Retrospective Analysis Of the Patients Samples (N)mentioning
confidence: 99%
“…Previous studies indicated that 50% of the HPV transient infections disappear within a few months in most cases, despite the presence of oncogenic virus, probably as a result of a competent host immune response [25,26].…”
Section: Retrospective Analysis Of the Patients Samples (N)mentioning
confidence: 99%
“…Dois elementos responsivos a glucocorticóides (GRE) também são conhecidos por mediar uma resposta a progesterona . A ativação de URR por progesterona e a inibição por anti-progesterona RU 486 têm sido demostradas in vitro 36 . Há ainda especulação a respeito da existência de um elemento responsivo a estrógeno (ERE) baseada na ativação de URR do HPV16 por estrógeno em células SiHa 37 .…”
Section: Figura 1 Esquema Representativo Do Genoma Do Hpv -16unclassified
“…O presente artigo de revisão explora os possíveis co-fatores do HPV na gênese do carcinoma escamoso do colo uterino, levando em conta apenas os fatores cuja associação com o vírus ou câncer cervical tenha sido documentada experimentalmente, e não apenas clínica ou epidemiologicamente. Dentre os 2,6,16,34,36,40,42,47,52,55 , bem como pelo esforço recente de pesquisadores no desenvolvimento de vacinas contra este vírus, com a finalidade de prevenção deste tipo de câncer 26,30,45,52 . A partir daí, esta revisão passa a explorar os possíveis co-fatores do HPV no processo de carcinogênese, levando em conta apenas os fatores cuja a associação com o vírus ou câncer cervical tenha sido documentada experimentalmente, e não apenas clínica ou epidemiologicamente.…”
unclassified
“…İnsan papilloma virüsü birçok şekilde bulaşmakta-dır; kontamine yüzeylerden, ciltteki lezyonlardan ve doğum kanalından olmak üzere direkt veya indirekt olarak bulaş görülmektedir 21 . Ancak, en önemli bulaş şekli cinsel yolla bulaştır 22 .…”
Section: Hpv Enfeksiyonunda Bulașunclassified
“…Enfekte hücre öncül kök hücreden ayrılarak epitelin diğer tabakalarına girer 20 . Daha sonra viral gen ifadesi minimal düzeydedir ve özellikle E6 ve E7 onkogenlerinin ifadesi E6/E7 transkriptleri ile sıkı bir kontrol altındadır 21 . Enfekte keratinosit farklıla-şan tabakalara girdiğinde, hücre döngüsünden ayrılır.…”
Section: Hpv Enfeksiyonunun Klinik Belirtileriunclassified